A ESCOLA PÚBLICA FRENTE ÀS REFORMAS EDUCACIONAIS: desafios da gestão democrática na rede pública estadual de São Luís do Maranhão - Costa, Waldirene Aparecida Oliveira da (2012)
The present study intended the analysis of the school facing educational reforms, taking as parameter democratic management in public schools of Sao Luis, Maranhao Brazil, whose goal was to apprehend this context through social, political and economic management, legal foundations, challenges and perspectives that pervade democratic management in public schools. Documents from the Ministry of Education and Culture, and some documents with the Secretary of Education of the State of Maranhao were used, in addition to literature on the subject, examined in books, articles, dissertations, theses, books and universities websites. The outline of this reality in public schools was analyzed using the above-mentioned documents and interviews with administrators, teachers, coordinators and representatives of parents, participants in this research. The study found that progress in building a democratic perspective of management in public schools is nonexistent and will be effective only in the extent that the State Education Office organize their management approach, defining their management model, and define the model expects to adopt to their schools, considering its current management model doesn t allow large margins of autonomy, because they are submitted to centralized and bureaucratic guidelines. Relatively to school management, was found that the role and function exercised by manager is a constant challenge to the school, because the manager is directed to democracy practice required both by official documents, as along with their faculty and administration. The challenge to managers is to act as a motivator and transformer, led to build a new school, which involves issues of solidarity and democratic, placing it in perspective of critical education and citizen, without, however having objective conditions for all changes recommended in official documents, as is subject to the practices imposed by the Education Secretary. The study found that the manager doesn t have a position to deliberate and lead alone, which constitutes the act of constant challenge to bring the school to community and their environment, linking strategic actions to structure the school to make a political and pedagogical, thereby building with the School Board, the Political Pedagogical Project which is the "face of the school". The study concluded that one of the main difficulties experienced by the school is the lack of involvement of most of school staff. It is understood that many of the actors of the school does not give credit to the institution where they work, because of false promises from government that occur in the public schools for decades. In this study it was noticed that the little involvement of counsel is directed only to financial issues of accountability and school lunches, prevailing here again, and the bureaucratic aspects at the expense of pedagogical issues.